Letter from the United States Department of State to Ernst Berl, September 29, 1938 - United States. Department of State (1938)
Letter to Ernst Berl (1877-1946) from an unknown author at the United States Department of State. The letter thanks Berl for his offer to assist the U.S. government and congratulates him for his impending naturalization to the United States.
Keywords: United States. Department of State; Berl, Ernst, 1877-1946; Emigration and immigration; Naturalization